The Relationship between Motor Skills and Physical Activity Patterns of Students with Disabilities in Special Schools - Mumin, Cep; Nurudin, Ahmad Alwi; Saleh, Muhammad (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
The research employs a quantitative descriptive method with a correlational design, involving 20 students (15 boys and 5 girls) from SLB Negeri Mutiara Bahari Mandiri, Sukabumi, selected through purposive sampling. Data collection utilized the Movement Assessment Battery for Children Second-editions (MABC-2) to measure motor skills and the Physical Activity Questionnaire for Children (PAQ-C) to assess physical activity levels. Results revealed an average motor skill score of 54.85, classified as